A double life : discovering motherhood - Harper, Lisa Catherine, 1966- (River teeth literary nonfiction prize (Series), 2011)
Motherhood splits a woman's life forever, into a before and an after. Harper brings her sense of humor as she explores the emotional and biological transformations that motherhood entails, and documents her own journey across this great divide.